2000
DOI: 10.1063/1.372636
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and structural properties of (CoxFe100−x)50Pt50 alloy thin films

Abstract: A study of magnetic and structural properties of (CoxFe100−x)50 (0≦x≦100) alloy thin films as functions of composition and substrate deposition-temperature Ts is carried out. The intrinsic perpendicular magnetic anisotropy Ku starts to increase with deposition temperature Ts for all the films (0≦x≦100) at about TS=250–300 °C, and then becomes nearly constant. The maximum values of Ku at room temperature thus obtained are 6×107, 4×107, and 2×107 erg/cc for Fe50Pt50, (Co43Fe57)50Pt50 and Co50Pt50, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(70 citation statements)
references
References 10 publications
1
67
0
Order By: Relevance
“…The Curie temperatures of the L1 0 FePt phase are strongly composition dependent and are higher than that of Fe 3 Pt phase. The abnormal dependence of M s at room temperature on x is caused by the low T C of Fe 3 Pt phase with x = 75-79. It was also found that there is a big difference in T C when measured through the heating and cooling thermomagnetic curves of the Fe-Pt alloys with x = 78-90.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Curie temperatures of the L1 0 FePt phase are strongly composition dependent and are higher than that of Fe 3 Pt phase. The abnormal dependence of M s at room temperature on x is caused by the low T C of Fe 3 Pt phase with x = 75-79. It was also found that there is a big difference in T C when measured through the heating and cooling thermomagnetic curves of the Fe-Pt alloys with x = 78-90.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Near x = 75 large volume instability ͑Invar effect͒ is observed in the L1 2 Fe 3 Pt phase ͑␥ 1 ͒. 5,6 The most recent interests in FePt nanostructured materials have been focused on the ferromagnetic L1 0 FePt phase ͑␥ 2 ͒ because of their potential applications in ultrahigh-density magnetic recording 7,8 and advanced permanent magnets 9,10 due to its very high uniaxial magnetocrystalline anisotropy and high Curie temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, a correlation has been indicated between the long-range order (LRO) parameter and the magnetocrystalline anisotropy energy. 3,4) Hence the LRO parameter is a key factor when the hard magnetic properties of these L1 0 ordered nanoparticles are discussed. As for the small isolated alloy nanoparticles with the ordered phase, particle size dependence of the order-disorder transformation temperature has been indicated and the stabilization of the high-temperature disorder phase due to downsizing has been reported in experimental results on several alloy systems.…”
Section: Introductionmentioning
confidence: 99%
“…STM images with atomically resolved chemical contrast are presented and the system's magnetic properties are analyzed by x-ray magnetic circular dichroism (XMCD). We show that depending on the specific lateral coordination of Fe the magnetism of these surface alloys (SA) can exhibit large out-of-plane magnetic anisotropy, comparable to that of high-anisotropy bulklike FePt alloy films (10-100 nm thickness) [4][5][6], and noncollinear magnetism due to DM interactions. While in bulk FePt large anisotropies are due to noncubic 3D stacking of Fe and Pt layers [7,8], we find a substantially different mechanism for SAs.…”
mentioning
confidence: 99%